The postpartum effect of maternal diabetes on the circulating levels of sirtuins and superoxide dismutase. Issue 2 (8th January 2018) - Sultan, Samar; Alzahrani, Nada; Al‐Sakkaf, Kalthoom
Abstract : Gestational diabetes mellitus (GDM) is a glucose intolerance disorder which occurs during pregnancy as a result of insulin insensitivity; it usually disappears after delivery. However, some women with GDM can develop type 2 diabetes (T2D) after delivery, and the mechanisms by which this occurs remain unknown. This study compared the levels of sirtuins (NAD‐dependent deacetylases) and antioxidative enzymes in postpartum women with previous GDM (pGDM) or T2D and in postpartum women with a previous healthy pregnancy (controls). Women with pGDM showed upregulated levels of sirtuin 1 (SIRT1) mRNA and protein, with reduced expression levels of sirtuin 3 ( SIRT3 ) and superoxide dismutase 2 ( SOD2 ), relative to the controls. Women with T2D similarly showed a lower level of SIRT3 mRNA than the controls. Lipid peroxidation (malondialdehyde) was higher in women with pGDM than in the controls. These data show that in women with pGDM, the reduced level of SIRT3 may play a role in the reduced SOD2 level, possibly leading to oxidative stress, which, in turn, upregulates the level of SIRT1 . These results might confer the risk of future diabetes development in women with pGDM, as a similar reduction in SIRT3 was found in women with T2D. Abstract : We tested the effect of previous gestational diabetes mellitus (pGDM) on the levels of sirtuins and antioxidative enzymes postpartum. We showed that women with pGDM had reduced sirtuin 3 ( SIRT3 ) and superoxide dismutase 2 ( SOD2 ) levels and upregulated SIRT1 relative to controls. This suggests that reduced SIRT3 level may play a role in the reduced SOD2 level, possibly leading to oxidative stress, which, in turn, upregulates the SIRT1 level. As women with type 2 diabetes also had reduced SIRT3, these results might confer the risk of future diabetes development in women with pGDM.